Acute Toxicity Test of Black Rice and Soybean Extract Complex - Liza Syafitri; Nina Salamah; Ichwan Ridwan Rais; Kintoko Kintoko; Sri Mulyaningsih; Moch Saiful Bachri (Jurnal Ilmiah Farmako Bahari, 2026)
The present study was conducted to assess the acute oral toxicity of a copigment complex formulated from extracts of black rice (Oryza sativa L., indica) and soybean (Glycine max (L.) Merr.). Despite extensive individual pharmacological investigations of these botanical sources, no safety data have previously been documented for their combined copigment complex intended as a functional beverage constituent. Following the Acute Toxic Class methodology (OECD 423), the complex was orally administered as a single dose at 300, 2000, or 5000 mg/kg body weight (BW) to female Swiss Webster mice (n=3 per dose group), alongside a vehicle control group administered 1% Na-CMC. A comprehensive 14-day monitoring program assessed mortality, a range of clinical indicators (including tremor, convulsions, salivation, diarrhea, lethargy, locomotion, coat condition, and ocular appearance), and body weight at Days 0, 7, and 14. No animal deaths occurred across any group. Transient, mild hypoactivity was noted in animals receiving 5000 mg/kg at 1–2 hours post-dose, which resolved completely by 4 hours post-administration. No additional adverse clinical manifestations or weight loss were detected. Based on these findings, the median lethal dose (LD50) is projected to surpass 5000 mg/kg BW, corresponding to GHS Category 5 (practically non-toxic). The results collectively establish a safety foundation for the use of this copigment complex as a functional ingredient in isotonic beverage products, while acknowledging the need for further subchronic and chronic toxicological investigations.